The Impact of AI Adoption on Professional Judgment in Auditing Practices (gjstudies, 2021)
The integration of artificial intelligence (AI) into auditing practices represents aparadigm shift, fundamentally altering the nature of professional judgment—the cornerstone of the auditing profession. While existing literature predominantly focuses onthe efficiency and accuracy gains from AI, this research investigates a more nuanced andunderexplored consequence: the transformation of the auditor’s cognitive role and theemergence of a new, hybrid form of judgment we term ’augmented professional judgment.’ This paper presents findings from a longitudinal, multi-method study involving147 auditors across Big Four and mid-tier firms, combining quantitative analysis of audit decision logs with in-depth qualitative interviews and cognitive task analysis. Weintroduce a novel theoretical framework that conceptualizes the auditor-AI interactionnot as a simple tool-use relationship, but as a dynamic cognitive coupling. Our resultsreveal a tripartite impact: (1) a significant reallocation of cognitive effort from routinedata processing to complex anomaly interpretation and hypothesis generation, (2) theemergence of new cognitive biases specific to AI-augmented environments, including’automation complacency’ and ’algorithmic anchoring,’ and (3) a critical dependencyon the auditor’s ability to maintain ’meta-judgment’—the capacity to critically evaluate and contextualize AI-generated insights. Contrary to fears of deskilling, we findevidence of a skill bifurcation; while procedural skills diminish in importance, skillsin probabilistic reasoning, AI literacy, and ethical oversight become paramount. Thestudy concludes that successful AI adoption in auditing hinges not on replacing humanjudgment, but on strategically redesigning audit processes to foster synergistic humanAI collaboration, thereby elevating, rather than eroding, the professional judgmentthat underpins audit quality and public trust. This research provides original contributions to the fields of auditing, human-computer interaction, and the philosophy ofprofessional expertise in the age of intelligent systems.